Nahdlatul Ulama sebagai Aktor Keagamaan dalam Resolusi Konflik Sosial Perspektif Perdamaian Global - Abdul Chamid; Nuriya Hamida (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2026)
This research aims to analyze and synthesize literature related to the role of Nahdlatul Ulama (NU) as a religious actor in the resolution of social conflicts from the perspective of global peace. This study uses a systematic literature review (SLR) approach with the adaptation of the PRISMA protocol. The results of the synthesis identify four central themes: first, the value of wasatiyyah (Islamic moderation) as an ideological foundation that is operationalized in conflict resolution practice; second, the role of NU as a multi-level mediator in communal conflicts in Indonesia; third, the transformation of NU into a global peacebuilding actor through the consolidation of the international network of moderate clerics; and fourth, the projection of NU's religious soft power in global peace governance. This study proposes a new concept of autonomous religious soft power to explain the unique capacity of moderate Islamic organizations to influence the dynamics of international peace without relying on state apparatus.   Penelitian ini bertujuan untuk menganalisis dan mensintesis literatur yang berkaitan dengan peran Nahdlatul Ulama (NU) sebagai aktor keagamaan dalam resolusi konflik sosial dari perspektif perdamaian global. Penelitian ini menggunakan pendekatan systematic literature review (SLR) dengan adaptasi protokol PRISMA. Kriteria inklusi penelitian mencakup publikasi ilmiah periode 1990–2024. Hasil sintesis mengidentifikasi empat tema sentral: pertama, nilai wasatiyyah (moderasi Islam) sebagai fondasi ideologis yang dioperasionalisasikan dalam praktik resolusi konflik; kedua, peran NU sebagai mediator multi-level dalam konflik komunal di Indonesia; ketiga, transformasi NU menjadi aktor peacebuilding global melalui konsolidasi jaringan ulama moderat internasional; dan keempat, proyeksi religious soft power NU dalam tata kelola perdamaian global. Kajian ini mengusulkan konsep baru autonomous religious soft power untuk menjelaskan kapasitas unik organisasi Islam moderat dalam mempengaruhi dinamika perdamaian internasional tanpa bergantung pada aparatur negara. Temuan ini berkontribusi pada pengembangan Islamic social thought, teori civil society berbasis agama, dan studi resolusi konflik dalam perspektif global.